Evidence that continuous normothermic blood cardioplegia offers better myocardial protection than intermittent hypothermic cardioplegia. - Grech, E. D. (1995)
OBJECTIVES--To compare transmyocardial ischaemia and oxidative stress, as well as non-infarction myocardial injury, in patients randomised to intermittent hypothermic cardioplegia or continuous normothermic blood-potassium cardioplegia. DESIGN--Prospective randomised trial. SETTING--Tertiary cardiac referral centre. METHODS--24 patients undergoing elective coronary artery bypass surgery were randomised to hypothermic (13 patients, mean (SEM) age 59.5 (2.6) years) or normothermic (11 patients, mean (SEM) age 59.7 (3.3) years) cardioplegia. Transmyocardial oxidative stress and ischaemia were assessed by the difference in plasma concentrations of oxidised glutathione and lactate respectively, from samples taken simultaneously from the coronary sinus and aortic root. Blood samples were taken just before cross clamp application and at intervals up to 15 min after cross clamp release. Non-infarction myocardial injury was assessed by measurement of creatine kinase MB isoenzyme activity from peripheral venous blood taken 2 and 18 h after surgery. RESULTS--Intermittent hypothermic cardioplegia resulted in a significant increase in transmyocardial ischaemia (P < 0.001) and oxidative stress (P < 0.001). Evidence of significantly increased myocyte damage was also present (P < 0.01). No significant corresponding changes were present with normothermic cardioplegia. CONCLUSIONS--Normothermic blood cardioplegia seems to avoid significant changes in myocardial ischaemic status and consequent oxidative stress. This study provides direct evidence that normothermic cardioplegia offers enhanced myocardial protection compared with that of hypothermic cardioplegia. Certain subsets of patients may derive more benefit from normothermic cardioplegia, although it is unclear whether this would be the case for all patients.